Helping Scholars Overcome Socioeconomic Barriers to Medical and Biomedical Careers: Creating a Pipeline Initiative. Issue 4 (7th August 2020) - Crews, Deidra C.; Wilson, Katherine L.; Sohn, Jungsan; Kabacoff, Cathryn M.; Poynton, Sarah L.; Murphy, Laura R.; Bolz, Jessica; Wolfe, Andrew; White, Paul T.; Will, Catherine; Collins, Chiquita; Gauda, Estelle; et al.
Abstract: Problem: To achieve their potential in medical and biomedical careers, students (scholars) from under-resourced backgrounds must build sophisticated skills and develop confidence and professionalism. To flourish in an advanced educational system that may be unfamiliar, these scholars also need networks of mentors and role models. These challenges can affect scholars at multiple stages of their education. Intervention: To meet these challenges, we created a broad and innovative biomedical research-focused pipeline program: the Johns Hopkins Initiative for Careers in Science in Medicine (CSM Initiative). This initiative targets three levels: high school, undergraduate, and post-baccalaureate/pre-doctoral (graduate and medical). We provide training in essential academic, research, professional, and social skills to meet the unique challenges of our scholars from under-resourced backgrounds. Scholars also build relationships with mentors who provide career guidance and support. We present an overview of the training and assessment at each level of this initiative. Context: The initiative took place at an institution located in the greater Baltimore area and that is endowed with exceptional doctoral and postdoctoral trainees, staff, and faculty including clinicians, physician-scientists, and scientists who served as key role models and mentors. Our pipeline program draws from local high school students and a local and national pool of undergraduates and post-baccalaureates preparing for medical or graduate school. Impact: Our goals for the high school scholars are significant improvement in academic skills, increased confidence, and matriculation into higher education systems. Currently, at least 83% of high school scholars have matriculated into four-year college programs and 73% have chosen science, technology, engineering, math, and medicine (STEMM)-related majors. Among undergraduate participants, 42% have matriculated thus far into medical or biomedical graduate programs and this number is expected to rise as more scholars graduate from college and either enter graduate training or pursue STEMM careers. Another 25% have returned to our post-baccalaureate program. Among post-baccalaureate scholars, 71% have now matriculated into doctoral-level graduate biomedical programs (medical or graduate school) and the remaining 29% are pursuing careers in STEMM-related fields such as biomedical research with some still aiming at graduate-level education. Our long-term goal is to see a large majority of our scholars become successful professionals in medicine, biomedical research, allied healthcare, or other STEMM fields. Analysis of the early phases of the CSM initiative demonstrates such outcomes are attainable. Lessons Learned: This program provides experiences in which scholars develop and practice core competencies essential for developing their self-identity as scientists and professionals. The most important lesson learned is that mentorship teams must be highly dynamic, flexible, thoughtful, and personal in responding to the wide range of challenges and obstacles that scholars from under-resourced backgrounds must overcome to achieve career success.